GTP-Dependent FlhF Homodimer Supports Secretion of a Hemolysin in Bacillus cereus - Mazzantini, Diletta; Fonnesu, Rossella; Celandroni, Francesco; Calvigioni, Marco; Vecchione, Alessandra; Mrusek, Devid; Bange, Gert; Ghelardi, Emilia (Frontiers in Microbiology, 2020)
The multidomain (B-NG) protein FlhF, a flagellar biogenesis regulator in several bacteria, is the third paralog of the signal recognition particle (SRP)-GTPases Ffh and FtsY, which are known to drive protein-delivery to the plasma membrane. Previously, we showed that FlhF is required for Bacillus cereus pathogenicity in an insect model of infection, being essential for physiological peritrichous flagellation, for motility, and for the secretion of virulence proteins. Among these proteins, we found that the L2 component of hemolysin BL, one of the most powerful toxins B. cereus produces, was drastically reduced by the FlhF depletion. Herein, we demonstrate that B. cereus FlhF forms GTP-dependent homodimers in vivo since the replacement of residues critical for their GTP-dependent homodimerization alters this ability. The protein directly or indirectly controls flagellation by affecting flagellin-gene transcription and its overproduction leads to a hyperflagellated phenotype. On the other hand, FlhF does not affect the expression of the L2-encoding gene (hblC), but physically binds L2 when in its homodimeric form, recruiting the protein to the plasma membrane for secretion. We additionally show that FlhF overproduction increases L2 secretion and that the FlhF/L2 interaction requires the NG domain of FlhF. Our findings demonstrate the peculiar behavior of B. cereus FlhF, which is required for the correct flagellar pattern and acts as SRP-GTPase in the secretion of a bacterial toxin subunit.